2018
DOI: 10.12659/msm.912065
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 199a Is Downregulated in Patients After Coronary Artery Bypass Graft Surgery and Is Associated with Increased Levels of Sirtuin 1 (SIRT 1) Protein and Major Adverse Cardiovascular Events at 3-Year Follow-Up

Abstract: BackgroundThe cardioprotective protein SIRT1 is elevated in patients with coronary artery disease (CAD) to compensate for the disease-related adverse effects, but less is known about the prognostic role of SIRT 1 regulating microRNAs in patients after coronary artery bypass graft (CABG) surgery.Material/MethodsThe expression of the SIRT 1-specific microRNAs miR-199a and miR-195 was analyzed using real-time PCR in 68 patients referred for CABG surgery and 34 control patients undergoing heart valve surgery. In C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
(47 reference statements)
0
20
0
1
Order By: Relevance
“…resting endothelial cells express no or low levels of adhesion molecules and are resistant to leukocyte recruitment. However, various cHd stimulants, including TnF-α, il-1β or oX-ldl, activate the endothelial inflammatory cascade (41). The present study revealed that overexpression of miR-381 significantly promoted oX-ldl-induced HuVec proliferation, decreased apoptosis and suppressed the inflammation response, whereas downregulation of mir-381 exhibited the opposite effect.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…resting endothelial cells express no or low levels of adhesion molecules and are resistant to leukocyte recruitment. However, various cHd stimulants, including TnF-α, il-1β or oX-ldl, activate the endothelial inflammatory cascade (41). The present study revealed that overexpression of miR-381 significantly promoted oX-ldl-induced HuVec proliferation, decreased apoptosis and suppressed the inflammation response, whereas downregulation of mir-381 exhibited the opposite effect.…”
Section: Discussionmentioning
confidence: 48%
“…a previous study demonstrated that mirnas serve important roles in many biological activities, including cell proliferation, inflammation and apoptosis (38). in cHd, mir-423, mir-23 and mir-199a have been reported to serve as biomarkers for therapeutic targets (39)(40)(41). mir-381 has been reported to be dysregulated in various cancers (20)(21)(22), but few studies have focused on the role of mir-381 in cHd.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of miRNA-92a attenuates oxidative stress and improves endothelial function through enhancing HO-1 expression and activity in diabetic mouse aortas [138]. Yamac et al observed markedly lowered expression of miRNA-199a in patients with coronary artery disease [139]. In parallel, they also showed the induction of cardioprotective protein SIRT1, a potential target of miRNA-199.…”
Section: Coronary Artery Diseases (Cad)mentioning
confidence: 98%
“…Endothelial cell apoptosis under oxidative stress plays a critical role in the initiation and progression of atherosclerosis [131][132][133][134][135][136][137][138][139][140][141]. Li et al observed that overexpression of miRNA-210 caused inhibition of apoptosis and reduction of ROS level in human umbilical vein endothelial cells (HUVECs) treated with H 2 O 2 and also downregulation of caspase levels.…”
Section: Coronary Artery Diseases (Cad)mentioning
confidence: 99%
See 1 more Smart Citation